Voices after dark a study on communication patterns of rape survivors - Florentino, Judith Ann P.
This study focused on the communication patterns of rape survivors: before and after rape occured. With this, the role of communication in the survivor's coping process was further examined. Moreover, their perception on media treatment towards them was also put into consideration. Data was gathered through the conducted interviews among three rape survivors, four of their relatives/friends and four therapists/counselors/social worker. In determining the communication patterns and coping strategies among rape survivors right after the incident, interviews with all the informants yielded the necessary data regarding this level of communication. The focus interviews with the informants provided relevant information on this study's aim to know their perception on media treatment and their view on life after the incident. The study found out that survivors have the tendency to be aloof and be quiet right after the incident. As much as possible they want to keep the case to themselves. Only when they could no longer bear the trauma alone and when they are confronted by others (since unusual acts can be seen from them), can they have the guts to talk about it to their loved ones. It is also evident from the study that communication is really important in order for survivors to cope with their situation. By constantly communicating with others, survivors will be able to release their inner thoughts and feelings, things that keep bugging and haunting them. With that, they would still feel accepted by many in spite of everything. Informants also viewed media negatively. They believe that media sometimes tend to exaggerate. Instead of helping those who are right, things would turn out differently, it is a matter of who are influential and powerful and who are not. The people rely on the information they give and since they sometimes give unfair and too sensationalized reports, there is the tendency to misled everyone.